2015
DOI: 10.1007/s00216-015-8925-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and single-laboratory validation of a method for the determination of flavonolignans in milk thistle seeds by high-performance liquid chromatography with ultraviolet detection

Abstract: Seeds of milk thistle, Silybum marianum (L.) Gaertn., are used for treatment and prevention of liver disorders and were identified as a high priority ingredient requiring a validated analytical method. An AOAC International expert panel reviewed existing methods and made recommendations concerning method optimization prior to validation. A series of extraction and separation studies were undertaken on the selected method for determining flavonolignans from milk thistle seeds and finished products to address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The superior efficiency and the improved peak symmetry and resolution of core-shell columns, when compared to the most common monolithic columns, for the analysis of the silybin (A and B) diastereoisomers were already described [ 22 , 23 , 41 ]. Moreover, the core-shell technology is enough versatile to allow for an easier possible transition of the present protocol to other methodologies, such as UPLC [ 41 , 42 , 43 , 44 ]. The typical LC-MS chromatogram (with detection set at 280 nm) is presented in Figure 2 and Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The superior efficiency and the improved peak symmetry and resolution of core-shell columns, when compared to the most common monolithic columns, for the analysis of the silybin (A and B) diastereoisomers were already described [ 22 , 23 , 41 ]. Moreover, the core-shell technology is enough versatile to allow for an easier possible transition of the present protocol to other methodologies, such as UPLC [ 41 , 42 , 43 , 44 ]. The typical LC-MS chromatogram (with detection set at 280 nm) is presented in Figure 2 and Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The chemical compositions of two sources of milk thistle seeds were extracted with 100% methanol and analyzed by Mudge and others. Silychristin, silydianin, silybin A, silybin B, isosilybin A, and isosilybin B were detected (Mudge et al, 2015). Choe et al identified several major chemicals in milk thistle seed flour as well.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The detection is carried out with UV detector at 280 nm (Nadeem, Taj Khan, Khan, & Ajmal Shah, 2020). For quantification of lignans, many simple (i.e., 13 C NMR spectroscopy; Nam, Paoli, Castola, Casanova, & Bighelli, 2011) or advanced techniques coupled with HPLC have been applied (Mudge, Paley, Schieber, & Brown, 2015;Table 4). For instance; Chen et al (2019) developed a simple and rapid method based on matrix solid-phase dispersion (MSPD) combined with silica gel and eluted with methanol and HPLC, where HPLC-MS/MS triple quadrupole was also utilized for the quantification of lignans found in espresso coffee.…”
Section: Lignans and Flavonolignansmentioning
confidence: 99%
“…For quantification of lignans, many simple (i.e., 13 C NMR spectroscopy; Nam, Paoli, Castola, Casanova, & Bighelli, 2011) or advanced techniques coupled with HPLC have been applied (Mudge, Paley, Schieber, & Brown, 2015; Table 4). For instance; Chen et al.…”
Section: Techniques Of Identification and Quantificationmentioning
confidence: 99%